2023
DOI: 10.1186/s40168-023-01702-y
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of host and habitat in determining the microbial communities of plant-feeding true bugs

Zi-Wen Yang,
Jiu-Yang Luo,
Yu Men
et al.

Abstract: Background The true bugs (Heteroptera) occupy nearly all of the known ecological niches of insects. Among them, as a group containing more than 30,000 species, the phytophagous true bugs are making increasing impacts on agricultural and forestry ecosystems. Previous studies proved that symbiotic bacteria play important roles in these insects in fitting various habitats. However, it is still obscure about the evolutionary and ecological patterns of the microorganisms of phytophagous true bugs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…However, the taxonomic remarks are reported as collective data considering the occurrence of fungi in soil and in association with insect pests, which does not allow us to infer specific associations with the latter [180]. Likewise, in an investigation concerning plant-feeding true bugs (Heteroptera: Cimicomorpha and Pentatomomorpha) carried out in China, data were summarized with reference to the family, not allowing us to infer the associations of Cladosporium with every single bug species [181].…”
Section: Taxonomic Aspects and Occurrencementioning
confidence: 99%
“…However, the taxonomic remarks are reported as collective data considering the occurrence of fungi in soil and in association with insect pests, which does not allow us to infer specific associations with the latter [180]. Likewise, in an investigation concerning plant-feeding true bugs (Heteroptera: Cimicomorpha and Pentatomomorpha) carried out in China, data were summarized with reference to the family, not allowing us to infer the associations of Cladosporium with every single bug species [181].…”
Section: Taxonomic Aspects and Occurrencementioning
confidence: 99%
“…Based on their anatomical features, members of the Miridae, or plant bugs, are not thought to be associated with any speci c gut symbiont. Recent studies, however, revealed that plant bugs possess diverse microorganisms in their gut [11][12][13][14][15], some of which are commonly found in or even speci c to host plant bug species [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their anatomical features, members of the Miridae, or plant bugs, are not thought to be associated with any speci c gut symbionts. Recent studies, however, revealed that plant bugs possess diverse microorganisms in their gut [13][14][15][16][17], some of which are commonly found in or even speci c to host plant bug species [16].…”
Section: Introductionmentioning
confidence: 99%